National Policies and Strategies - Breisinger, Clemens; Nicol, Alan (CGIAR Initiative on National Policies and Strategies, 2023)
National Policies and Strategies aims to enhance the coherence of policy engagement across CGIAR Initiatives, building shared analytical capacity at national and subnational levels, developing communities of policy practice, responding to policy demand and supporting rapid crisis response (see graphic). These activities will inform more effective and efficient country-level policymaking, benefiting millions more people, including the poorest and most food insecure living in vulnerable environments.